2006
DOI: 10.1152/ajprenal.00488.2005
|View full text |Cite
|
Sign up to set email alerts
|

Increased glomerular permeability to negatively charged Ficoll relative to neutral Ficoll in rats

Abstract: It is established that the glomerular filter sieves macromolecules based on their size, shape, and charge. Anionic proteins are thus retarded compared with their neutral or cationic counterparts. However, recent studies have indicated that charge effects are small, or even "anomalous," for polysaccharides. We therefore investigated the impact of charge on the glomerular permeability to polysaccharides by comparing sieving coefficients (theta; primary urine-to-plasma concentration ratio) for negatively charged,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
76
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 30 publications
0
76
0
Order By: Relevance
“…We do not report a "degree of substitution" as other investigators have, because we do not have data allowing estimation of charge-to-mass ratio of CM-Ficoll (3,20). The degree of substitution measured by titration in a polydisperse solution only yields an aggregate sense of how charged the solutes are.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We do not report a "degree of substitution" as other investigators have, because we do not have data allowing estimation of charge-to-mass ratio of CM-Ficoll (3,20). The degree of substitution measured by titration in a polydisperse solution only yields an aggregate sense of how charged the solutes are.…”
Section: Discussionmentioning
confidence: 99%
“…Opposing that coherent body of theory and experiment are other data suggesting that some of the apparent charge selectivity may be artifactual, due to cellular processing of charged solutes (7). More recent papers demonstrate both enhanced transport of anionic tracers compared with neutral ones and in vivo studies in which reducing the charge of the basement membrane gel had negligible effect on permselectivity to albumin (3,6,20,22,35). At least one group, Rippe and colleagues (3), has suggested that enhanced transport of carboxymethylated Ficoll might be explained by conformational changes instead of electrostatics; that is, the modification process by which an anionic charged Ficoll is produced causes the Ficoll to become less compact and more flexible.…”
Section: Discussionmentioning
confidence: 99%
“…27 This is consistent with reports showing the ficoll becomes more open when a negative charge is added. 28 This is most likely due to the opposing negative electrostatic charges repelling each other, forcing the structure to open. Given that neutral dextrans exist in a relatively open structure, they may have been less likely to change their configuration in response to an altered surface charge.…”
Section: Diffusion In Free Solutionmentioning
confidence: 99%
“…Asgeirsson et al demonstrated an increased permeability of the glomerular capillary wall to negatively charged carboxymethylated ficoll, relative to neutral ficoll. 28 This occurs because the negatively charged ficoll becomes larger, 28 and whilst the increased molecular radius might be anticipated to slow diffusion across tissue, the molecule instead becomes less dense and consequently more flexible (compressible), making it hyperpermeable across the glomerular barrier. By contrast, dextran did not show this marked increase in hyperpermeability when carboxymethylated.…”
Section: Net Surface Chargementioning
confidence: 99%
“…This may be of some concern especially when one is dealing with modified dextrans or Ficoll since the modifications are amenable to alter the tertiary configuration of these macromolecules and thereby . In this regard, an anomalously "increased" transglomerular passage of "anionic" Ficoll was observed relative to "neutral" Ficoll, which in theory if this situation is applied to the globular proteins should have a "decreased" GUU value (1). In view of these concerns, Sverrisson et al cautiously used "conformationally unchanged" or "intact Ficoll" with varying hydrodynamic radii as functional tracers for their experiments; however, minor changes in the tertiary conformation may still not be detectable.…”
mentioning
confidence: 90%